Dforce : Safety devices dealer / Mohamad Najib Mohd Diah ... [et al.] - Mohd Diah, Mohamad Najib; Azmi, Mohammed Fikry Ashraf; Wan Muhabakri, Wan Mubaraq; Mohamad Zahari, Khairunisa; Basri, Khuraisha
Our company based on "dealer'' principle which means we act as a middle person between the supplier and the customer. In this particular business we focus on safety and security devices such as anti-riot vest and bulletproof vest. For instance we bid in tender for safety purpose by supplying the products for some needed places. Another example to get the tender is by connecting the inside person who used to know about the tender and can inform us earlier about it. We believe this type of company business can promise us better future and income to stand as the business is still in small range of competition in Malaysia. There were a few company that well-known in Malaysia with the same business nature such as Sapura Holdings, Deftech Sdn Bhd and Softlabs Sdn Bhd. These companies are already known as the well running company. As one of the beginner in this prospect of industry we can use them to be as guider to achieved our goal as well to be a successful and well-known company just like them. In order to market our company, we used benchmarking method and referred to best company as learn from the expert. We also compare about strength and weaknesses of several companies to get the best conclusion and results. By using this kind of method, we believe we will manage to give challenge to existed company and one day we will be one of the concrete stand company in Malaysia. If possible all around the world.